Educational Process of Medical Students in Basic Sciences in Birjand University of Medical Sciences - Zohreh Khazaie; Thayebeh Khazaie; Meisam Babaie (Kerman University of Medical Sciences, 2009)
Background & Objective : Identifying faculty members educational needs and level of their skills in teaching affairs would improve planning for faculty members development and sublimity This study was performed to assess attitude of faculty members who are teaching practical courses towards their educational needs and level of skills in teaching methods of practical courses Methods : In this descriptive study 83 faculty members teaching practical courses in Isfahan University of Medical Sciences were selected by stratified random sampling and completed a reliable and valid questionnaire consisted of 14 items about educational needs and skill level of teaching methods in practical courses Results : The mean (±SD) score of faculty members skill level was 271(±04) out of four Faculty members skill level was low (mean score less than 25) in analysis and interpretation of the test questions (389%) evaluation methods of practical skills (535%) designing performance tests (528%) and making educational films (479%) Mean (±SD) total score of educational needs was 345(±089) out of five According to these results faculty members were in need of all 14 aforementioned items Educational needs included critical thinking motivating methods and information resources in order of priority Conclusion : Faculty members expressed need for education and improving their skills in teaching practical courses Considering mentioned educational needs and skills it seems that teaching method and student assessment workshops need to be revised and the content of the workshops should be designed according to faculty members educational needs together with implementing different educational methods